Dampak Pandemi COVID-19 Dan Price Book Value Terhadap Return Saham - Stefi, Claudia; Oktorina, Megawati (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2024)
COVID-19 emerged as a worldwide pandemic starting in late 2019. The world economy experienced a major shock and many businesses and corporations went out of business due to the impact of this pandemic. Stock markets in all countries around the world are also experiencing turbulence and extraordinary price fluctuations. This study examines the effect of the COVID-19 pandemic and the Price Book Value ratio on stock returns in Indonesia. The data analysis method uses multiple linear regression methods on stocks that are members of the LQ45 index from 1 January 2020 to 26 November 2021. The results of this study indicate that the increase in COVID-19 cases and Price Book Value has a significant negative effect on stock returns. The results of this study provide empirical evidence that stock prices in the LQ45 index in Indonesia tend to decline when there is a significant increase in the COVID-19 case. Therefore, market participants can be more careful and cautious in taking their portfolio positions in investing in the Indonesian stock market during the COVID-19 pandemic. The limitations of this study show a low R2 coefficient, which means that many other variables still affect stock returns outside of this study. Future research can use other financial ratio variables, dividends and rights issues in explaining their effect on stock returns.